Modified sculpted composite resin iris pattern for customized ocular prosthesis - William Wijaya; Ariyani; Ricca Chairunnisa; Haslinda Z. Tamin (Indonesia Prosthodontic Association, 2023)
Patient with loss of eye demands natural ocular prosthesis for self-esteem and social intercourse. Iris texture and coloring technique are crucial procedure to recreate natural iris like the remaining eye. The purpose of this paper is to explain sculpting method using composite-resin to achieve natural iris pattern. A 29-year-old male came to Dental Hospital Universitas Sumatera Utara with chief complaint of demanding new ocular prosthesis because old ocular prosthesis had been used for 12 years, iris position was not good and not aesthetically pleasing. The modification is the use of a 12 mm diameter iris base made from light-cured composite resin then a thin layer of composite resin is placed evenly and texture of iris is sculpted directly on composite resin according to the designed pattern and then being light-cured again. Then coloring with acrylic paint according to the color of patient's left iris. The technique for du-plicating iris is highly dependent on the operator's ability, both in color selection and iris patterning. The use of com-posite resin make it easier to get a good texture of iris pattern so as to facilitate coloring process with the ultimate goal of achieving an aesthetically pleasing ocular prosthesis. Patient was satisfied with his new ocular prosthesis.